2000
DOI: 10.1110/ps.9.10.2001
|View full text |Cite
|
Sign up to set email alerts
|

Protein renaturation by the liquid organic salt ethylammonium nitrate

Abstract: The room-temperature liquid salt, ethylammonium nitrate~EAN!, has been used to enhance the recovery of denaturedreduced hen egg white lysozyme~HEWL!. Our results show that EAN has the ability to prevent aggregation of the denatured protein. The use of EAN as a refolding additive is advantageous because the renaturation is a one-step process. When HEWL was denatured reduced using routine procedures and renatured using EAN as an additive, HEWL was found to regain 75% of its activity. When HEWL was denatured and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
248
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(259 citation statements)
references
References 44 publications
8
248
1
2
Order By: Relevance
“…Ionic liquids have attracted much interest recently as solvents for biomolecules because they are nonaqueous solvents that are able to promote the self-assembly of amphiphiles (29), and they appear to stabilize protein function (30,31), and some can promote, inhibit, or solubilize amyloid fibrils (32)(33)(34). To date, only high concentrations of strong acids such as formic acid and TFA have been reported to depolymerize rodlets to the monomeric form (6).…”
Section: Resultsmentioning
confidence: 99%
“…Ionic liquids have attracted much interest recently as solvents for biomolecules because they are nonaqueous solvents that are able to promote the self-assembly of amphiphiles (29), and they appear to stabilize protein function (30,31), and some can promote, inhibit, or solubilize amyloid fibrils (32)(33)(34). To date, only high concentrations of strong acids such as formic acid and TFA have been reported to depolymerize rodlets to the monomeric form (6).…”
Section: Resultsmentioning
confidence: 99%
“…To probe this further, we carried out MSP3-heme interaction experiments in a buffer containing ammonium nitrate that did not favor aggregation of MSP3 as was shown by ThT or Congo Red assays (data not shown). A derivative of ammonium nitrate is a well known solute that disrupts aggregation of proteins (65). In the presence of ammonium nitrate, binding of heme was significantly reduced suggesting that heme binding somehow depends on the aggregation of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the activity of protease is highly maintained not only in water-immiscible aprotic ionic liquids but also in water-miscible aprotic ionic liquids as well [22,23]. On the other hand, it has been reported that protic ionic liquids keep the stability of proteins in an aqueous solution at high temperatures [24,25], and amyloid fibrils of proteins are dissolved in protic ionic liquids and are refolded by dilution with an aqueous solution [32]. Moreover, aprotic ionic liquids can refold the denatured protein [33].…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, C, protein aggregation is prevented, and any cloudy appearance is absent [25]. The hydrophobic core of lysozyme unfolded by heat interacts with the cation of ionic liquids, and cation adsorption results in acquisition of a net positive charge preventing aggregation via electrostatic repulsion [24]. Figure 4 shows the relationship between temperature and the remaining activity of lysozyme in aqueous solutions containing water-miscible ionic liquids after the heat treatment for 30 min.…”
Section: Thermal Inactivation Of Lysozymementioning
confidence: 99%
See 1 more Smart Citation